Gender and citizenship : - Siim, Birte (Cambridge University Press, 2000)
This book compares the links between women's social rights and democratic citizenship in three different citizenship models: republican citizenship in France, liberal citizenship in Britain, and social citizenship in Denmark. Birte Siim argues that France still suffers from the contradictions of pro-natalist policy, and that Britain is only just starting to reconceptualize the male-breadwinner model that is still a dominant feature. Examination of the dual-breadwinner model in Denmark reveals new research about Scandinavian social policy